2017
DOI: 10.1016/j.ijfatigue.2017.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue cracking behaviour of epoxy-based marine coatings on steel substrate under cyclic tension

Abstract: Strain controlled fatigue tests have been performed on two types of heavily filled epoxy corrosion protection coating sprayed onto a 6 mm steel substrate. Fatigue cycling was performed at R ratios of 0 and-1. The two coatings differed in their formulation and the major differences in mechanical performance were in their static strain to first crack development and their fracture toughness, where Coating A was significantly tougher than coating B. During strain cycling coating crack development was monitored us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Their results shows that add small concentrations of PMMA can enhance the resistance of epoxy coating to fatigue crack propagation rate. Wu et al [28] studied the fatigue cracking development morphology in epoxy coatings used for marine ships. They found that the development of crack in surface is started soon after the onset of cycling and continued growth of surface channeling cracks.…”
Section: Introductionmentioning
confidence: 99%
“…Their results shows that add small concentrations of PMMA can enhance the resistance of epoxy coating to fatigue crack propagation rate. Wu et al [28] studied the fatigue cracking development morphology in epoxy coatings used for marine ships. They found that the development of crack in surface is started soon after the onset of cycling and continued growth of surface channeling cracks.…”
Section: Introductionmentioning
confidence: 99%